HUBUNGAN PERSEPSI PENYAKIT DENGAN KUALITAS HIDUP PASIEN DIABETES MELLITUS TIPE 2 - Gusti Ayu Ary Ary Antari; Desak Made Widyanthari; Nyoman Agus Jagat Raya (Program Studi Sarjana Ilmu Keperawatan dan Profesi Ners, Fakultas Kedokteran, Universitas Udayana, 2016)
Quality of life is an important indicator which shows patient satisfaction in living with Type-2 Diabetes Mellitus (T2DM) and becomes ultimate goal of patient care. Illness perception is the main concept of common sense model that serves as the patient behavior determinant. Illness perception appears as an important element related to patient’s response to the diseases and its management, therefore a good illness perception will lead to an improvement of patient’s quality of life. This study aims to determine the relationship between illness perception and T2DM patients’ quality of life. This was a descriptive-analytic study with cross-sectional design done at Diabetes Community of West Denpasar II Public Health Center from October to November 2015. Patients with Type-2 Diabetes Mellitus (T2DM) aged ? 45 years were selected through purposive sampling. In order to determine the relation between illness perception and quality of life T2DM patients, simple linear regression analysis were performed. The results of this study showed that from 60 subjects most of them aged between 45-54 years old and suffered from T2DM < 5 years. The mean score for disease perception (IPQ-R Brief) was 32.92; while for quality of life (WHOQOL Brief) the mean score was 65.25. Simple linear regression analysis demonstrated that illness perception has significantly relationship with quality of life T2DM patient (r = 0,822; p = 0,000). Illness perception significantly affected quality of life of 67.6% (p=0.000), while the rest were influenced by other variables. The regression equation was Quality of life = 97,782 + 0,988illness perception. In conclusion, there was a relationship between illness perception and T2DM patient’s quality of life. These results can be further developed on the establishment of good illness perception to support quality of life T2DM patient. Keywords: Quality of life, Disease perception, IPQR Brief, WHOQOL Brief